MINAT SISWA DALAM MEMILIH PRODI PENDIDIKAN BAHASA JERMAN PASCA PEMBELAJARAN DI SEKOLAH - Syaputra, Arlian Fachrul; Angreany, Femmy; Mannahali, Misnah (J-EDu: Journal - Erfolgreicher Deutschunterricht, 2025)
The purpose of this study is to investigate and describe students' interest in choosing a German Language Education Study Program after participating in German language learning at school. This study used a quantitative descriptive approach. The sample in this study was 116 students from seven schools obtained using purposive sampling. The instrument in this study is a questionnaire consisting of several aspects related to interest in learning and interest in continuing studies in the German Language Education Study Program. The results of this study show that, the majority of students (82%) have a passion and 66% of students also have sufficient interest in learning German. There are several aspects that attract students' attention in learning German, namely the ability to speak and communicate with a percentage level of 41%. However, students' interest and passion in learning German is not directly proportional to continuing their studies to the German Language Education Study Program, there are only 11% of students who have an interest and there are 34% of students who have no interest and 55% of students who are still in doubt. There are several causes of the lack or doubt of student interest, namely the existence of greater interest in other study programs, lack of information about the major or study program, lack of support from parents, and lack of career opportunities. The findings in this study indicate that although students' interest in learning German is high, it cannot directly encourage students' interest in continuing to the same major or study program in college.